Pengaruh Penggunaan Media Video Pembelajaran terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI di SMPN 2 Ampek Angkek - Aditio Wahyu Rifaldi; Salmi Wati; Wedra Aprison; Charles Charles (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This investigation was motivated by the low average academic achievement of Islamic Religious Education students at SMPN 2 Ampek Angkek. In the 2022/2023 academic year, the low midterm exam scores of students in class IX 1 of SMPN 2 Ampek Angkek provided empirical support for the statement. A total of 25 student responses were received for the exam; however, only five students achieved the minimum score of 75 required to complete SMPN 2 Ampek Angkek. A prospective approach to improving Islamic Religious Education learning outcomes at SMPN 2 Ampek Angkek is to incorporate video media into the established curriculum. This study aims to determine whether the application of video media affects the academic achievement of Islamic Education students at SMPN 2 Ampek Angkek. The purpose of this study is to determine whether or not there is an effect of the application of video media at SMPN 2 Ampek Angkek on PAI learning outcomes. The purpose of this study is to determine whether the adoption of video media has an impact on the academic achievement of PAI students at SMPN 2 Ampek Angkek. This research was categorised as a pseudo-experiment and used posttest control group design as the only research methodology. The student participants in this study were members of grade IX. In this investigation, purposive sampling, a type of non-probability sampling, was used. The experimental class in this study consisted of students of grade IX 3, while the control class consisted of students of grade IX 1. Data for this investigation was collected through assessment of students' progress in Islamic Religious Education. The Sig α value was ascertained to be 0.00 ± 0.05, based on the results of hypothesis testing conducted using SPSS software. Thus, it can be concluded that the utilisation of video media is able to influence the academic achievement of Islamic Religious Education students attending SMPN 2 Ampek Angkek.